Optimalisasi Pembelajaran Model Qiroati Dalam Meningkatkan Kemampuan Membaca Al-Quran Sebagai Standar Kelulusan Siswa - Faridah Nurul Hakim; Maslani; Miftahul Fikri (UIN Sunan Gunung Djati Bandung, 2022)
This article is intended to find out the problems faced by students and teachers in using the qiroati model of SD Al-Hidayah Majalengka, the teacher's efforts and the steps taken in overcoming these problems. By using a qualitative-descriptive method, this study resulted in a conclusion; First, the qiroati model is a model for reading the Quran that applies the principles of fluent, fast, precise, and correct with 3 steps, namely the initial classical with teaching aids, individual, and the final classical. Second, the qiroati learning process at SD Al-Hidayah Majalengka was carried out in 2 shifts, students were grouped by level and only carried out with the classical tadarrus together and individually with the evaluation results still running optimally. Third, the improvement process through the use of the qiroati learning model is seen from the achievements of students at each grade level and the number of students' graduations in the Al-Quran Final Stage Learning Evaluation (EBTAQ) exam.